2011
DOI: 10.1007/s00464-011-1615-3
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic sleeve gastrectomy as a revisional option after gastric band failure

Abstract: Our results suggest that LSG is safe, feasible, and effective as a revisional procedure for failed LAGB and can be considered as an appealing option in these cases. Larger series and longer follow-up are needed to confirm this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Leak rates in patients undergoing revisional bariatric procedures are higher than those reported for primary cases [27,28]. Three of the 6 patients had had previous surgical intervention in the upper stomach region making this a logical risk factor for development of GBF.…”
Section: Discussionmentioning
confidence: 42%
“…Leak rates in patients undergoing revisional bariatric procedures are higher than those reported for primary cases [27,28]. Three of the 6 patients had had previous surgical intervention in the upper stomach region making this a logical risk factor for development of GBF.…”
Section: Discussionmentioning
confidence: 42%
“…On the other hand, Iannelli [21] reported some increased risk for post-secondary LSG complications and was followed in by others [20,[22][23][24][25][26][27][28]. Gagniere et al [24] reported a series of 102 patients undergoing primary or secondary LSG, with significantly higher risk for complications in the secondary LSG group.…”
Section: Discussionmentioning
confidence: 96%
“…Short-and mid-term outcomes appear promising, with some even approaching those seen with LRYGBP. Increasingly, the sleeve also is used as a revisional procedure for patients who have failed weight loss after LAGB or vertical band gastroplasty (VBG) [30,31].…”
Section: Discussionmentioning
confidence: 99%